HYPERTENSION IN THE ELDERLY: CHALLENGES IN MANAGEMENT AND TREATMENT - Dhiman, Sanjay; Chourasia, Anurag (International Journal of Research -GRANTHAALAYAH, 2024)
Hypertension is a prevalent and significant health issue among the elderly, contributing to increased risks of cardiovascular diseases, stroke, and kidney failure. Managing hypertension in older adults poses unique challenges due to age-related physiological changes, comorbidities, and polypharmacy. This review explores the complex pathophysiology of hypertension in the elderly, including age-related changes in vascular function and the impact of comorbid conditions. It examines the difficulties in diagnosing hypertension, such as variability in blood pressure readings, white coat syndrome, and masked hypertension, highlighting the need for accurate monitoring through home and ambulatory techniques. The review discusses current management strategies, emphasizing the importance of setting appropriate treatment goals, implementing lifestyle modifications, and utilizing pharmacological treatments, including new antihypertensive drugs and combination therapies. It also addresses challenges such as adverse drug reactions, medication adherence, and the management of polypharmacy. Recent advances, including innovations in drug delivery systems and digital health technologies, offer promising solutions for improving hypertension management. Future research directions include exploring precision medicine, understanding the role of the gut microbiome, and addressing health disparities. Clinicians are advised to adopt personalized treatment approaches, integrate technological tools, and address socioeconomic barriers to optimize hypertension management in the elderly. This review underscores the need for ongoing research and tailored strategies to improve outcomes and quality of life for older patients with hypertension.